A retrospective cohort study of oral anticoagulant treatment in patients with acute coronary syndrome and atrial fibrillation - Yan Zhang; Linlin Mai; Yu Wu; Jianjing Luo; Xinyue Liu; Hailan Zhu; Haoxiao Zheng; Guoquan Liang; Yuli Huang (BMJ Open)
Objective To examine the real-world patterns of oral anticoagulant (OAC) therapy in patients with acute coronary syndrome (ACS) and atrial fibrillation (AF) in Southern China undergoing percutaneous coronary intervention (PCI) and determine the clinical characteristics associated with OAC prescription.Design A retrospective cohort study.Setting This study was conducted in the Shunde Hospital, Southern Medical University and the second hospital of Zhaoqing, China, from January 2013 to 31 December 2018.Participants Patients were aged ≥18 years, hospitalised for ACS and received PCI treatment.Outcome measures AF was diagnosed based on an ECG recording or a Holter monitor. Prescription of OACs and antiplatelets were determined from the discharge medication list.Results A total of 3612 patients with ACS were included: 286 (7.9%) were diagnosed with AF, including 45 (1.2%) with paroxysmal AF, 227 (6.3%) with persistent/permanent AF and 14 (0.4%) with unclassified AF. Although 95.5% of patients with AF were at high risk (CHA2DS2-VASc score ≥2) of stroke, only 21.7% of them were discharged on OACs (10.5% received warfarin and 11.2% received non-vitamin K antagonist OACs). Patients with pre-admission use of OAC, a HAS-BLED score <3, with persistent/permanent AF were more likely to receive OAC treatment at discharge.Conclusion We found that approximately 8% of patients who underwent PCI during ACS hospitalisation also demonstrated AF. Anticoagulant therapy was greatly underused. Patients with paroxysmal AF and an increased risk of bleeding were less likely to receive anticoagulant treatment. Further efforts should be made to increase the adherence to guideline recommendations for OACs.